Concept Attainment Worksheet to Enhance Concept Knowledge and Science Process Skills in Physics Instruction - Rani, S. A.; Wiyatmo, Y.; Kustanto, H. (Jurnal Pendidikan IPA Indonesia, 2017)
This research aims to: (1) produce conceptual attainment worksheet; (2) know concept understanding improvement; and (3) know science process skills improvement. This was a development research by using 4-D models (define, design, develop, and disseminate). The development product was tested in grade XI of SMA Negeri 1 Magelang with 20 students for limited test and 33 students for field test. The research produced worksheet based on validator’s score from language structure and design PA 96.97%, appropriate learning with conceptual attainment method PA 95.24%, and learning to improve science process skills PA 95%, in which all aspects got the best category. Almost students agreed to the worksheet with presentation 78% for limited test and 89% for field test. Conceptual understanding improvement based on normalized gain was 0.56 for limited test and 0.50 for field test. The improvement of science process skills wasn’t significant for all the test with range 0.1-0.3.